2017
DOI: 10.1038/sc.2016.191
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of laser-evoked potentials and quantitative sensory testing in the diagnosis of neuropathic spinal cord injury pain: a multiple case study

Abstract: As QST is a psychophysical examination depending on patient cooperation, we suggest that the combination of QST and LEP might be a valuable diagnostic tool to detect lesions of the somatosensory system in a subgroup of patients with neuropathic spinal cord injury pain and inconclusive MRI findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 62 publications
0
15
0
Order By: Relevance
“…Previous studies have shown that thermal thresholds were either higher (Gruener, Zeilig, Laufer, Blumen, & Defrin, 2016) or lower (Kumru et al, 2012) in subjects with SCI and NP (SCI-NP) compared to those without NP (SCI-nonNP). A combination of QST and evokedpotentials were considered a useful objective tool to investigate somatosensory function in SCI-NP subjects (Landmann, Berger, Stockinger, & Opsommer, 2017) and CHEPs can be utilised as a sensitive marker of spinal cord pathology, that is, myelopathy (Jutzeler et al, 2017) and provides both subjective and objective readouts of spinothalamic tract integrity. Moreover, prior neuroimaging studies have provided evidence of structural and functional cortical reorganisation that accompany SCI (Athanasiou et al, 2017;Nardone et al, 2013Nardone et al, , 2018Solstrand Dahlberg, Becerra, Borsook, & Linnman, 2018) and pain (including NP; Alomar & Bakhaidar, 2018;Apkarian, Bushnell, Treede, & Zubieta, 2005;Kuner & Flor, 2016;Moisset & Bouhassira, 2007;Morton, Sandhu, & Jones, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that thermal thresholds were either higher (Gruener, Zeilig, Laufer, Blumen, & Defrin, 2016) or lower (Kumru et al, 2012) in subjects with SCI and NP (SCI-NP) compared to those without NP (SCI-nonNP). A combination of QST and evokedpotentials were considered a useful objective tool to investigate somatosensory function in SCI-NP subjects (Landmann, Berger, Stockinger, & Opsommer, 2017) and CHEPs can be utilised as a sensitive marker of spinal cord pathology, that is, myelopathy (Jutzeler et al, 2017) and provides both subjective and objective readouts of spinothalamic tract integrity. Moreover, prior neuroimaging studies have provided evidence of structural and functional cortical reorganisation that accompany SCI (Athanasiou et al, 2017;Nardone et al, 2013Nardone et al, , 2018Solstrand Dahlberg, Becerra, Borsook, & Linnman, 2018) and pain (including NP; Alomar & Bakhaidar, 2018;Apkarian, Bushnell, Treede, & Zubieta, 2005;Kuner & Flor, 2016;Moisset & Bouhassira, 2007;Morton, Sandhu, & Jones, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that thermal thresholds were either higher (Gruener, Zeilig, Laufer, Blumen, & Defrin, 2016 ) or lower (Kumru et al, 2012 ) in subjects with SCI and NP (SCI‐NP) compared to those without NP (SCI‐nonNP). A combination of QST and evoked‐potentials were considered a useful objective tool to investigate somatosensory function in SCI‐NP subjects (Landmann, Berger, Stockinger, & Opsommer, 2017 ) and CHEPs can be utilised as a sensitive marker of spinal cord pathology, that is, myelopathy (Jutzeler et al, 2017 ) and provides both subjective and objective readouts of spinothalamic tract integrity.…”
Section: Introductionmentioning
confidence: 99%
“…The neurological assessment of an SCI contains pinprick testing as a proxy for STT function 1 . This clinical bedside testing can be complemented with thermal stimulation, in particular cold and warm detection thresholds, to test STT integrity [17][18][19][20] . In addition to bedside examination tools used in the clinical work-up of spinal lesions, electrophysiological methods including pain-related evoked potentials provide objective evidence of preserved somatosensory function 21,22 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, neurophysiological measures can help to evaluate the integrity of relevant spinal tracts. Well established techniques include somatosensory evoked potentials (SSEP) for examining lemniscal functions, contact heat evoked potentials (CHEPS) and laser evoked potentials (LEP) for testing nociceptive and thermoreceptive tracts and motor evoked potentials (MEP) for assessing the corticospinal tract [ 43 ], [ 44 ], [ 45 ], [ 46 ], [ 47 ], [ 48 ], [ 49 ], [ 50 ]. Statement 4.3 The Quantitative Sensory Testing (QST) may be considered in case of uncertainty concerning the interpretation of symptoms with respect to neuropathic pain [ 51 ], [ 52 ], [ 53 ], [ 54 ].…”
Section: Resultsmentioning
confidence: 99%